Serial tissue Doppler imaging in the evaluation of bronchopulmonary dysplasia-associated pulmonary hypertension among extremely preterm infants: a prospective observational study - Gopagondanahalli, Krishna Revanna; Abdul Haium, Abdul Alim; Vora, Shrenik Jitendrakumar; Sundararaghavan, Sreekanthan; Ng, Wei Di; Choo, Tze Liang Jonathan; Ang, Wai Lin; Binte Mohamad Taib, Nur Qaiyimah; Wijedasa, Nishanthi Han Ying; Rajadurai, Victor Samuel; Yeo, Kee Thai; Tan, Teng Hong (Frontiers in Pediatrics, 2024)
Objectives: To evaluate the serial tissue Doppler cardiac imaging in the evolution of bronchopulmonary dysplasia-associated pulmonary hypertension (BPD-PH) among extremely preterm infants. Design: Prospective observational study. Setting: Single-center, tertiary-level neonatal intensive care unit. Patients: Infant born <28 weeks gestation. Main outcome measures: Utility of TDI in the early diagnosis and prediction of BPD PH and optimal timing for screening of BPD PH. Results: A total of 79 infants were included. Seventeen (23%) infants had BPD PH. The mean gestational age was 25.9±1.1 weeks, birth weight was 830 ±174gm. The BPD PH group had a high incidence of hemodynamically significant PDA (83% vs 56%, P <0.018), longer oxygen days (96.16±68.09 vs 59.35±52.1, p < 0.008), and prolonged hospital stay (133.8±45.9 vs 106.5±37.9 days, p <0.005). The left ventricular eccentricity index (0.99±0.1 vs 1.1±0.7, p<0.01) and the ratio of acceleration time to right ventricular ejection time showed a statistically significant trend from 33 weeks (0.24±0.05 vs 0.28±0.05, p<0.05). At 33 weeks, the BPD PH group showed prolonged isovolumetric contraction time (IVCT) (27.84±5.5 vs 22.77±4, p<0.001) prolonged isovolumetric relaxation time (IVRT) (40.3±7.1 vs 34.9±5.3 p<0.003), and abnormal myocardial performance index (MPI) (0.39±0.05 vs 0.32±0.03, p <0.001). These differences persisted at 36 weeks post-conceptional gestational age. Conclusions: TDI parameters are sensitive in the early evolution of BPD PH. The diagnostic accuracy can be increased by combining with conventional echocardiographic parameters. The BPD PH can be recognizable as early as 33-34 weeks of gestation.